Risk factors for surgical site infection after patellar fracture surgery in the elderly - Hui Qi; Wei Duan; Ruili Jia; Shuai Wang; Ming An; Yubin Long (Journal of Orthopaedic Surgery and Research)
Abstract Background Patellar fractures are a common knee injury among elderly patients, with a high risk of developing surgical site infections (SSI) postoperatively, which severely affects patient prognosis and quality of life. Elderly patients are more susceptible to SSI due to various factors such as decreased immune function and chronic diseases. Therefore, identifying the risk factors for SSI is of great clinical significance for prevention. Objective This study aims to analyze the risk factors for postoperative SSI in elderly patients with patellar fractures, providing a basis for developing more effective clinical prevention and treatment strategies. Methods This retrospective study collected data from 856 elderly patients who underwent patellar fracture surgery at Baoding First Central Hospital between January 2017 and December 2023. Patients were divided into SSI and non-SSI groups based on the occurrence of SSI, and their demographic data, comorbidities, and laboratory results were analyzed. Logistic regression was used to identify independent risk factors for SSI, and ROC curve analysis was conducted to determine the optimal cutoff point for predictive indicators. Results The incidence of SSI was found to be 2.1%. Univariate analysis showed that BMI, surgical delay, diabetes, hematocrit (HCT), and albumin (ALB) were significantly associated with SSI. Logistic regression analysis further confirmed that BMI (p = 0.043), surgical delay (p = 0.000), HCT (p = 0.038), ALB (p = 0.015), and diabetes (p = 0.022) were independent risk factors for SSI. ROC curve analysis indicated that the optimal cutoff points for BMI, HCT, and ALB were 25.39 kg/m2, 35.62%, and 39.3 g/L, respectively, with an AUC of 0.794 for the combined predictive indicators. Conclusion High BMI, surgical delay, diabetes, low HCT, and low ALB are independent risk factors for postoperative SSI in elderly patients with patellar fractures. Preoperative management targeting these high-risk factors, such as optimizing patient weight, controlling diabetes, and improving nutritional status, can effectively reduce the incidence of SSI and improve postoperative outcomes. Future multicenter studies may further validate these findings and provide additional prevention strategies.